Mal'chishki - Gabrilyan, Alexander (Russia : Tatiana Konstantinova, 2005)
A film about the first Chechen campaign between 1994 -1995 from the perspective of a soldier. The documentary attempts to shed light upon how the soldiers were involved in these events, what they were fighting for, and who they were dying for during the war.
Verzio Film Festival Submission